Assessing the change in severity levels of psychiatric comorbidities and quality-of life of married-females before and after hysterectomy- A 1 month follow-up study - Malvika Dahuja; Piyush Mahajan; Manjit Singh; Anisetty Visweswara Rao (Telangana Journal of Psychiatry)
Introduction: Hysterectomy either improves or worsens psychiatric symptoms and quality of life (QoL). Objectives: (1) To estimate the prevalence of psychiatric comorbidities and related factors in married females undergoing hysterectomy. (2) To compare the severity of psychiatric symptoms at baseline, after 1 week, and 1 month of hysterectomy. (3) To compare the level of QoL at baseline, after 1 week, and 1 month of hysterectomy. (4) To estimate the sociodemographic profile of married females undergoing hysterectomy. Materials and Methods: A cohort study was conducted in the Departments of Psychiatry and Gynecology, Subharti Medical College, Meerut, Uttar Pradesh, from 2015 to 2017, consisting of 100 married females of 30–60 years of age group who were undergoing hysterectomy. They were diagnosed on their baseline psychiatric comorbidities and psychiatric rating scales: Hamilton Anxiety Rating Scale, Hamilton Depression Rating Scale, and World Health Organization Quality of Life-BREF Scale were applied on all the patients 1 week prior to hysterectomy to assess their baseline severity and their level of QoL. The data regarding their anemic status were also recorded. The patients were reassessed after 1 week and 1 month of hysterectomy for any change in severity of their psychiatric symptoms and QoL. Results: In our study, the mean age of patients was 40.54 ± 0.83 years. Fifty-six percent of patients were educated, 56% lived in rural areas, 60% were Hindus, 54% belonged to joint families, 48% were farmers, and 58% belonged to lower–middle class. Fifty percent of patients had depressive episode, 30% had generalized anxiety disorder, and 20% had somatoform disorder. The mean age of marriage was 20.32 ± 0.40 years. The mean age of hysterectomy was 40.54 ± 0.83 years. The decision of hysterectomy was taken after great suffering because of apprehension for hysterectomy (10%), self-image (10%), husband not ready (50%), and family not ready (30%). Fifty-eight percent of them were anemic. The indications of hysterectomy were fibroid uterus – 42%, pelvic inflammatory disease – 20%, endometriosis – 18%, vaginal prolapse – 12%, and adenomyosis – 8%. Fifty-four percent of patients underwent transabdominal hysterectomy, 42% underwent transvaginal hysterectomy, and 4% underwent laparoscopic hysterectomy. When they were compared in follow-up period posthysterectomy, the baseline anxiety symptoms did not improve after 1 week (P = 0.13) but improved after 1 month of hysterectomy (P = 0.01). The depressive symptoms improved after 1 week (P = 0.03) and 1 month of hysterectomy (P = 0.01). QoL reduced after 1 week (P = 0.03) but finally improved after 1 month of hysterectomy (P = 0.01). Conclusion: Gynecological conditions have various associated psychiatric morbidities and definitely impacts QoL. Hence, a timely taking decision for hysterectomy limits and improves psychiatric symptoms quickly and improves QoL.